Socialist Exploitation of the Worker in the First Half of the 1950s: a Case Study of the H. Cegielski Industry Plant in Poznań - Jankowiak, Stanisław (Studia Historiae Oeconomicae, 2024)
Building the "foundations of the socialist system" meant intensive industrialization in the economy, with an emphasis on heavy industry, which was to be achieved mainly at the expense of the standard of living and working conditions of workers. By adopting unrealistic indicators, political and administrative methods were used to force employees to make more effort, without compensating it with the amount of earnings. Various methods were used: one of the elements of exploitation was low wages, or even the so-called “starvation wages” for some of the workers. The authorities suggested the possibility of increasing them through additional work. In this case, labor competition or long-term production commitments were initiated. On the other hand, the working time needed to produce specific products was administratively shortened, standards were constantly raised, etc. As a result of these activities, the living conditions of employees not only did not improve but even deteriorated. It turned out that the socialist employer is not at all different from the capitalist, and sometimes is even worse than him, because he has a greater range of possibilities of pressure and, in case they resist, of repression. By paying starvation wages, the system kept the rest of the profit earned for its own needs. He was also blind in looking at the real problems, most often looking for a mythical “enemy” or activist party members. Exploited beyond measure, the workers tried in every way to limit this exploitation, hence the abysmal quality of production, huge consumption of materials, widespread waste or simply avoiding work. The party's methods of activation proved ineffective, which the Poznań workers reminded the authorities of on 28 June 1956 by taking to the streets.